WAKTU PANEN YANG TEPAT MENENTUKAN KANDUNGAN GULA BIJI JAGUNG MANIS (Zea mays saccharata ) - SURTINAH SURTINAH (Universitas Lancang Kuning, 2008)
ABSTRAKThe research was done experimentaly which used completely the randomizeddesign, and the design of treatment is the age of harvest that consist of 6 times ofharvest, there are the age 55 days, the age 60 days, 65 days, 70 days, 75 days, and theage 80 days, of harvest. The parametre that observed are the amount of leafs, thelength of cob, the weight of cob leavy, the weight cob without leaf, the seed sugarcontent, and the content of seed moisturizer. The result of this research shown thatthe different of age harvest really influence for all the parametre determine. And the ageharvest that gives the highest sweet corn seed sugar content is 70 days after planting.